PENGARUH EARNING PER SHARE DAN PRICE BOOK VALUE TERHADAP HARGA SAHAM PADA PT ASTRA INTERNATIONAL TBK PERIODE 2014-2023 - Diana, Diana; Nurcahayati, Siti (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze the effect of Earning Per Share (EPS) and Price Book Value (PBV) on stock prices at PT Astra International Tbk for the period 2014–2023. The research method used is a quantitative approach, with data analysis techniques including descriptive statistics, classical assumption tests, multiple linear regression analysis, model feasibility tests, and hypothesis testing using SPSS version 31. The data used are secondary data obtained from the annual financial reports of PT Astra International Tbk and stock price data published through the Indonesia Stock Exchange. The sample in this study includes all company financial reports over the past ten years. The results of the study show that partially, Earning Per Share (EPS) does not have a significant effect on stock prices, as indicated by the t value (0.809) < t table (2.365) and a significance value of 0.445 > 0.05. Meanwhile, Price Book Value (PBV) has a positive and significant effect on stock prices, supported by a t value (3.710) > t table (2.365) and a significance value of 0.008 < 0.05. Simultaneously, EPS and PBV have a significant effect on stock prices, with an Fvalue (8.914) > Ftable (4.737) and a significance value of 0.012 < 0.05. These results indicate that both fundamental variables together are able to explain the variation in the stock prices of PT Astra International Tbk during the research period.